Exploitation of Stall Owners at Bengkok Pinang Market - Ahmad Murodi; Seno Santoso; andri kurniawan (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2024)
Traditional markets have an important role in the local economy, including in the Pinang Bangkok Market, which is the center of the community's trade activities. However, stall owners in this market face various challenges, such as competition with modern retail, limited capital, and lack of managerial and marketing skills. This study aims to analyze the empowerment strategy of stall owners to increase the competitiveness and sustainability of their business. The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. The results of the study show that empowerment can be carried out through business management training, access to capital, marketing digitalization, and the formation of a community of traders as a forum for sharing experiences and capacity building. In addition, the role of the government and related parties in providing supportive regulations and adequate infrastructure is also an important factor in the success of empowering kiosk owners. In conclusion, empowerment based on strengthening individual and collective capacity can improve the business sustainability of stall owners in the Bangkok Pinang Market.